New Media, New Generation and Social Capital - Pavićević, Olivera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
New media, which imply all forms of social communication on the Internet, are becoming a significant social factor in modern society. They are not only champions of technological change in the ways of communication, but are also producing a quality change in the relationship toward social interaction. Effects of new forms of interaction established in electronic social networking (Facebook, MySpace, etc.) are subjects of recent research. Final assessment of the effects of new media on the social capital has still not been made, but the emphasis is put on the examination of social groups made up of members of the younger generation because they appear to be the most frequent users of new social networks. The paper is an attempt to establish some issues of significance for examining the impact of new media on the social capital in the focus of changes, which include the young generation (high school and university students).